Surface roughness of a resin composite - Isabel, Carlos Alberto Camargo; Dominguette, Alexandre Augusto Sarto; Santos, Saulo Galvão Dos; Ribeiro, José Carlos Rabelo; MoysÉs, Marcos Ribeiro (Faculdade São Leopoldo Mandic, 2016)
ABSTRACTObjective: The aim of the present study was to evaluate the surface roughness (Ra) of the Z-350 resin composite following immersion in different media (distilled water, coca-cola, coffee, black tea and red wine).Methods: Fifty specimens of resin composite measuring 10 mm x 2 mm were prepared. Polymerization was performed using the conventional method (40 s). Each specimen was immersed for one hour per day. Evaluations were performed at baseline as well as after three, six, nine and 12 months. Three Ra readings were taken in opposite directions at each evaluation using a roughness meter. Mean Ra values were subjected to analysis of variance (ANOVA) followed by Tukey's test (p < 0.05).Results: A significant increase in Ra was found in the specimens submitted to coffee, coca-cola(r) and black tea between baseline and the three-month evaluation. Variance was also found among the remaining evaluation times (3 months to 12 months), but the differences did not achieve statistical significance. No statistically significant differences in Ra were found among evaluation times in the specimens submitted to red wine or distilled water.Conclusion: Based on the present findings, coca-cola, coffee and black tea exert an influence on the surface roughness of resin composites.

RESUMOObjetivo:Avaliar a rugosidade da superfície (Ra) do Z-350 resina composta após imersão em diferentes meios (água destilada, coca-cola, café, chá preto e vinho tinto).Métodos:Foram preparados cinquenta espécimes de resina composta medindo 10 mm x 2 mm. A polimerização foi realizada através do método convencional (40 s). Cada espécime foi imerso durante uma hora por dia. As avaliações foram realizadas na linha de base, bem como após três, seis, nove e 12 meses. Três leituras Ra foram levados em direções opostas em cada avaliação, utilizando um medidor de rugosidade. Os valores médios de Ra foram submetidos a análise de variância (ANOVA) seguido pelo teste de Tukey (p <0,05).Resultados:Um aumento significativo na Ra foi encontrada nas amostras submetidas ao café, coca-Cola(r) e chá preto entre o início e a avaliação de três meses. Variância também foi encontrado entre as épocas de avaliação restantes (3 meses a 12 meses), mas as diferenças não atingiram significância estatística. Não houve diferenças estatisticamente significativas na Ra encontrados entre os momentos de avaliação nos casos submetidos ao vinho tinto ou água destilada.Conclusão:Com base nos achados, coca-cola, café e chá preto exercem uma influência sobre a rugosidade superficial de resinas compostas.
Rugosidade superficial de resina composta
Keywords: Beverages; Immersion; Resin composite; Tooth erosion.; Bebidas; Imersão; Resinas compostas; Erosão dentária.